2012
DOI: 10.1021/ja305663k
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Molecular Sieve Separation of Ethylene/Ethane Mixtures with Silver Zeolite A

Abstract: Absolute ethylene/ethane separation is achieved by ethane exclusion on silver-exchanged zeolite A adsorbent. This molecular sieving type separation is attributed to the pore size of the adsorbent, which falls between ethylene and ethane kinetic diameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
121
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(127 citation statements)
references
References 19 publications
2
121
0
Order By: Relevance
“…Clearly, the pore limiting size (for the access of guest gas molecule into the MOF crystal) is 3.96 Å, while the largest cavity within the channel is 4.6 Å in diameter. Note that the empirical kinetic diameters of C 2 H 2 /C 2 H 4 are ∼3.3/4.2 Å (3.32 × 3.34 × 5.70 Å 3 for C 2 H 2 versus 3.28 × 4.18 × 4.84 Å 3 for C 2 H 4 ), respectively46474849. For ethylene, its kinetic diameter is slightly larger than the channel pore opening of UTSA-100a, and much larger than the interchannel window size.…”
Section: Resultsmentioning
confidence: 99%
“…Clearly, the pore limiting size (for the access of guest gas molecule into the MOF crystal) is 3.96 Å, while the largest cavity within the channel is 4.6 Å in diameter. Note that the empirical kinetic diameters of C 2 H 2 /C 2 H 4 are ∼3.3/4.2 Å (3.32 × 3.34 × 5.70 Å 3 for C 2 H 2 versus 3.28 × 4.18 × 4.84 Å 3 for C 2 H 4 ), respectively46474849. For ethylene, its kinetic diameter is slightly larger than the channel pore opening of UTSA-100a, and much larger than the interchannel window size.…”
Section: Resultsmentioning
confidence: 99%
“…In earlier works numerous researchers have reported the adsorption equilibrium and kinetics of ethane, ethylene and their mixtures on various adsorbents with different adsorption mechanisms. The most studied adsorbents are: activated carbons [11], zeolites [12][13][14][15][16], -complexation based adsorbents [17][18][19][20][21][22][23], and CMS [24]. Table S1 in the Supporting Information shows a concise summary of the main results obtained on these studies.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that some degree of weak π‐complexation exists between Ag + and N 2 , resulting in high N 2 /O 2 selectivity at low pressure and impeded N 2 desorption. Aguado et al further investigated the ethylene/ethane separation performance in AgX . Although the ethylene uptake capacity does not change much, the interaction between AgX and ethylene is intensified as indicated by the steep isotherm and elevated heat of adsorption with respect to NaX …”
Section: Zeolites For Adsorptive Light Olefin/paraffin Separationsmentioning
confidence: 92%